Enhancement of Oxytocin in the Medial Prefrontal Cortex Reverses Behavioral Deficits Induced by Repeated Ketamine Administration in Mice - Zhu, Weili; Ding, Zengbo; Zhang, Zhihui; Wu, Xiao; Liu, Xiaoya; Zhang, Ya; Li, Suxia; Zhou, Liping; Tian, Geng; Qin, Jing (Frontiers in Neuroscience, 2021)
Ketamine is a popular recreational substance of abuse that induces persistent behavioral deficits. Although disrupted oxytocinergic systems have been considered to modulate vulnerability to developing drugs of abuse, the involvement of central oxytocin in behavioral abnormalities caused by chronic ketamine has remained largely unknown. Herein, we aimed to investigate the potential role of oxytocin in the medial prefrontal cortex (mPFC) in social avoidance and cognitive impairment resulting from repeated ketamine administration in mice. We found that ketamine injection (5 mg/kg, i.p.) for 10 d followed by a 6-d withdrawal period induced behavioral disturbances in social interaction and cognitive performance, as well as reduced oxytocin levels both at the periphery and in the mPFC. Repeated ketamine exposure also inhibited mPFC neuronal activity as measured by a decrease in c-fos positive cells. Furthermore, direct microinjection of oxytocin into the mPFC reversed the social avoidance and cognitive impairment following chronic ketamine exposure. In addition, oxytocin administration normalized ketamine-induced inflammatory cytokines including TNF-α, IL-6, and IL-1β levels. Moreover, the activation of immune markers such as neutrophils and monocytes, by ketamine was restored in oxytocin-treated mice. Finally, the reversal effects of oxytocin on behavioral performance were blocked by pre-infusion of the oxytocin receptor antagonist atosiban into the mPFC. These results demonstrate that enhancing oxytocin signaling in the mPFC is a potential pathway to reverse social avoidance and cognitive impairment caused by ketamine, partly through inhibition of inflammatory stimulation.